Women playing men : Yue opera and social change in twentieth-century Shanghai - Jiang, Jin, 1954- (University of Washington Press, 2009)
Modern forces converge and gender roles are challenged in this volume that explores the influence of Yue opera - a subgenre of Chinese opera that transformed all-male opera into an all-female art forms, with women cross-dressing as male characters.